Studies of lattice mismatch and threading dislocations in GaAs/Si grown by MBE - Kaya, M; Atici, Y (Academic Press Ltd- Elsevier Science Ltd, 2004)
GaAs/Si(001) thin films with six Si interlayers grown by molecular beam epitaxy (MBE) were examined by transmission electron microscopy (TEM). The interface structure of the films was investigated by using both plan-view and cross-sectional TEM specimens. It was seen that the films have a smooth interface associating with misfit and threading dislocations between the GaAs epilayer and the Si substrate. It was also observed that the Si interlayers had an undulated shape reducing the threading dislocations in the structure. It was obtained that the strain relaxation at the interface occurs by misfit and threading dislocations. The g (.) b contrast experiments displayed 60degrees-type misfit dislocations with a/2 <110> {111} slip system in the structure. Electron diffraction experiments were also performed to find out the reduction of the lattice mismatch and the strain left in the structure using the cross-sectional GaAs/Si(001) samples. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: GaAs/Si thin films; strain relaxation; misfit and threading dislocations; TEM